Economic empowerment through strengthening the role of farmer groups in TNBTS - Setyo Tri Wahyudi; Nurul Badriyah; Rihana Sofie Nabella; Kartika Sari; R. Radeetha (Universitas Muhammadiyah Malang, 2023)
Bromo Tengger Semeru National Park (TNBTS) is one of the attractive natural tourist destinations in Indonesia, especially in East Java. Besides having natural wealth and beautiful scenery, TNBTS not only offers tourism, but also a fertile agricultural sector. However, the development and management of the sector has not yet been optimized so that it has not had an equitable impact on improving the economy of citizens and the welfare of the community, especially in Tosari District, Pasuruan Regency. Therefore, the purpose of this service is to empower the economy of the community in the Bromo Tengger Semeru National Park (TNBTS) Tosari District, Pasuruan Regency. The findings show that there are 9 farmer groups in the Tosari sub-district that have developed superior products, namely potatoes. The problems experienced by farmer groups in the Tosari sub-district are subsidized fertilizers and the weather that often changes. Another problem faced by farmers in Tosari District is the purchase of harvested goods at low prices by middlemen. So, in this case, the government needs to play a role in supplying subsidized fertilizers and educating farmers regarding climate change. Farmers' groups can synergize with Karang Taruna groups to market and promote Tosari's specialty processed products. Farmers' groups can also synergize with academics in making Tosari's specialty products.